2021
DOI: 10.21037/tlcr-20-760
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and multifaceted role of neutrophils in lung cancer

Abstract: Lung cancerLung cancer is regarded as a highly preventable disease, where the leading risk factor, cigarette smoking, accounts for approximately 80% of diagnoses. Cigarette smoke contains multiple classes of recognized carcinogens i n c l u d i n g b e n z o ( a ) p y r e n e s , p o l y c y c l i c a r o m a t i c hydrocarbons, and tobacco specific nitrosamines (1,2). Collectively, these compounds exert their genotoxic effects by forming DNA adducts and by generating reactive oxygen species (ROS) that cause m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 106 publications
0
37
0
Order By: Relevance
“…Kargl et al, found that neutrophil content in the TME negatively correlated with the presence of CD8+ and CD4+ T cells and with Th1 and Th17 subsets, but not with Treg cells, implicating a potential immune suppressive role for neutrophils in NSCLC (44,45). Data from preclinical studies in IL-17:K-Ras mutated transgenic mice demonstrated that resistance to anti-PD-1 therapy is abrogated by neutrophil depletion, reconstituting T cell activation (46).…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Kargl et al, found that neutrophil content in the TME negatively correlated with the presence of CD8+ and CD4+ T cells and with Th1 and Th17 subsets, but not with Treg cells, implicating a potential immune suppressive role for neutrophils in NSCLC (44,45). Data from preclinical studies in IL-17:K-Ras mutated transgenic mice demonstrated that resistance to anti-PD-1 therapy is abrogated by neutrophil depletion, reconstituting T cell activation (46).…”
Section: Immunosuppressionmentioning
confidence: 99%
“…The infiltration of phagocytes and Treg in tumors ultimately promotes tumor growth. The differentiation of TAN can be regulated by regulating cytokines and chemokines in the immune microenvironment, so that it mainly plays an anti-tumor effect in the liver immune microenvironment (28)(29)(30).…”
Section: Tumor-associated Neutrophilmentioning
confidence: 99%
“…Neutrophils are the dominant type of immune cell in the NSCLC tumor microenvironment (TME), to which they respond and polarize into distinct phenotypes that operate in an anti-tumorigenic or pro-tumorigenic manner [ 43 ]. The clinically relevant adverse impact of a neutrophil predominance, both systemically and in the TME of patients with NSCLC, is exacerbated by the negative prognostic value of both a persistent neutrophilia and a high neutrophil-to-lymphocyte ratio (NLR ≥ 5) [ 44 ].…”
Section: Circulating Immune Cellsmentioning
confidence: 99%